Pemilihan Kontrasepsi Oleh Aseptor Kb Selama Masa Pandemi Covid-19 dalam Menjaga Kesehatan Reproduksi di Wilayah Kerja Puskesmas Moncongloe Maros - Fitriani Fitriani; Jusni Jusni; Endang Astira (Jurnal Pengabdian Ilmu Kesehatan, 2021)
: Indonesia is a developing country with a large population. The population growth rate in Indonesia has increased by 1.49% or an increase of 4.5 million every year with a fairly large population, showing that Indonesia is not without population problems. So during the Covid-19 pandemic, it is necessary to emphasize the importance of using contraception and emergency contraception in maintaining reproductive health and emphasize the importance of using contraception and emergency contraception. So that family planning does not deviate from the planned path. This also supports maternal mental health, baby health and family welfare. The aim of this activity is to help PUS in choosing the type of contraception during the Covid-19 pandemic in maintaining reproductive health with counseling methods and assistance in choosing contraception. This community service activity has been successfully implemented. WUS in the Moncongloe Maros Health Center area have also received information about contraception, especially during the Covid-19 pandemic. Judging from the EFA response, this activity was welcomed and considered to have provided positive benefits during the pandemic.